To determine which points, if any, are solutions to the system of equations:
- \( y = 2x + 2 \)
- \( y = 2x - 4 \)
We can substitute the points to see if they satisfy both equations.
Check the point \( (0, -4) \):
Substituting \( x = 0 \) and \( y = -4 \) into both equations:
-
First equation:
\( y = 2(0) + 2 \)
\( -4 = 2 \) β Not true. -
Second equation:
\( y = 2(0) - 4 \)
\( -4 = -4 \) β True.
Since this point only satisfies the second equation and not the first, \( (0, -4) \) is not a solution for the system.
Check the point \( (0, 2) \):
Substituting \( x = 0 \) and \( y = 2 \) into both equations:
-
First equation:
\( y = 2(0) + 2 \)
\( 2 = 2 \) β True. -
Second equation:
\( y = 2(0) - 4 \)
\( 2 = -4 \) β Not true.
Since this point only satisfies the first equation and not the second, \( (0, 2) \) is not a solution for the system.
Since neither point is a solution, the correct response is:
Neither of these points are solutions.